Exercises in Ephemerality : positive death acceptance in life - Hsu, Li (2016)
Every one of us experiences an instinctual fear of death. For some of us, this fear manifests indirectly, either as generalized unrest or masquerading as another psychological symptom. In our death repressed society, the denial of death does nothing to assuage this shared fear. As such, many people are unsure of how to confront their own mortality, resulting in residual anxiety and unconscious destructive behavior.